Characterization of the equine microbiome during late gestation and the early postpartum period, and at various times during the estrous cycle in mares being bred with raw or extended semen - Jones, Emily (Kansas State University, 2019)
Two experiments were conducted to investigate the microbiome of the mare and foal in the late gestational to early postpartum period as well as the effects of breeding on the mare uterine and vaginal microbiota. In the first experiment the objectives were to investigate the microbial composition of the perinatal foal gut and its similarity to the maternal microbiome, and to characterize the temporal dynamics of the microbial composition of mare feces and the vagina during late gestation and the mare vagina and uterus during the early postpartum period. Nine Quarter Horse mare/foal pairs were utilized in this study. Starting 6 weeks prior to parturition, mare feces, vaginal swabs, and milk secretions were collected at 2-week intervals until parturition. At parturition, mare fecal, colostral and placental, and foal meconium samples were collected. Uterine efflux and vaginal swabs were collected from mares on day 7 and 25 postpartum. Samples were analyzed using NGS of the V4 region of the 16S rRNA gene to determine microbial composition. Analysis of sequencing data and statistics were performed using QIIME2 and R. The mare fecal and vaginal microbiomes were generally stable during late gestation. The neonatal foal gut was dominated by the Bacteroidetes and Firmicutes phyla as well as genera commonly found in adult feces. Meconium appeared to be more similar to mare feces and placenta than colostrum. In general, the postpartum mare uterine and vaginal microbiomes were stable postpartum and had many shared taxa with the placental microbiome. The equine neonate is born with a unique gut microbiome compared to dam feces, placenta and colostrum; however, the foal gut may be colonized in utero by some of the dam’s gut and uterine microbes. The objectives of the second experiment were to investigate the microbiome of the uterus and vagina in healthy mares and to determine the effect of breeding with either raw or extended semen on the uterine/vaginal microbiomes. Sixteen Quarter Horse mares and one stallion were utilized in this study. Mares were separated into 2 treatments: artificially inseminated (AI) with 10 mL of raw semen only (RAW, n=8) or 10 mL of semen and 10 mL of extender (EXT, n=8). Uterine efflux and vaginal swabs were collected when a follicle measuring ≥ 35 mm was first observed. Mares were then inseminated within 24 hours of initial sample collection and uterine and vaginal samples were collected again 48 hours post-AI. The uterine and vaginal protocol was repeated in the next estrous cycle. Feces were collected once from mares, immediately following the first detection of a follicle measuring ≥ 35 mm. Semen samples were collected for analysis prior to insemination. Samples were analyzed using the same protocol as the first experiment. Microbes were detected in all sample types. Feces and semen were distinct from all other sample types, however there were few differences between the uterine and vaginal microbiomes. The uterine microbiota was not significantly impacted by breeding and there were no differences between breeding with raw or extended semen. The vaginal microbiome did shift post-AI in the first cycle and between the first and second cycle. Although there were differentially abundant taxa between the uterus, vagina and semen, Actinobacteria, Bacteroidetes, and Firmicutes the were dominant phyla and Corynebacterium and Prophyromonas were dominant genera in all three sample types. In healthy mares the uterus appeared to return to the pre-AI microbial composition by 48 hours post-AI and there was no shift in composition between estrous cycles. However, the vaginal microbiome is dynamic and displays more shifts following breeding and throughout the estrous cycle than the uterine microbiota. The semen, vaginal and uterine microbiomes shared dominant taxa, indicating that there may be similar control mechanisms in mares and stallions to recognize commensal bacteria within the reproductive tract.
Keywords: Equine; Microbiome; Microbiota; Uterus; Vagina; Meconium